Pelaksanaan Pemilihan Gubernur Jawa Tengah Tahun 2018 Dalam Meningkatkan Partisipasi Politik Dengan Media Yang Tepat - Muhammad Fatchuriza; Teguh Adi Prasojo (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
To determine the precise media beforehand need to do research on the community.This study aims to provide an overview of the role of the media when combined with an understanding of the character of the community in order to increase the political participation of the community. Therefore, this research will be conducted qualitatively by using secondary data in the form of data from KPUD Central Java as well as other references related to previous research and Primary data derived from interviews with some communities in the community.